Effect of judo practice on the body composition of children and adolescents: A 9 month intervention - Miranda, Diego De Souza; Thamyres Ciccotti Saraiva, Bruna; Suetake, Vinícius Yukio Botelho; Alves, Davi Da Silva; Sousa, Daniel Eduardo Rodrigues De; Freitas Júnior, Ismael Forte; Christofaro, Diego Giulliano Destro (Universidade Estadual Paulista, 2017)
AbstractAims: To analyze the effects of 9 months of judo training on the body composition of children and adolescents.Methods: 105 children and adolescents aged between 5 and 15 years were divided into two groups: control (n=40) and Judo (n=65), all participants of one Philanthropic institution. Anthropometric measurements, total body composition, and body composition per region were performed using DEXA. The judo intervention lasted 9 months, held twice a week for one hour. The control group did not perform any type of training. Repeated measures ANOVA with adjustments for age, sex, and maturation, and the effect size by Eta Squared were performed. SPSS software version 13.0 was used and the statistical significance adopted was p-value<5%.Results: After the intervention, statistical significance was observed in body fat (kg) (p-value=0.031). There was an increase in BF in both groups; however this increase was much higher in the control group.Conclusion: The practice of 9 months of judo was effective for the maintenance of body fat in children and adolescents.
Keywords: martial arts; children; adolescents; physical activity; judo